Obesity and Climate Change: Can We Link the Two and Can We Deal With Both Together?. (May 2014) - Webb, Gary James; Egger, Garry
Obesity and climate change are 2 modern world dilemmas. However, despite an understanding of many of the causal factors relating to each, large-scale interventions have had minimal impact on either problem to date. Some behaviors associated with obesity (eg, processed food consumption, nonrenewable fuel use, etc) also affect greenhouse gas (GHG) emissions associated with climate change. This suggests that interventions aimed at curbing GHGs might also have public health benefits. Personal carbon trading is an emission reduction intervention that has been proposed to influence obesity-related behaviors. This article builds on the links between obesity and climate change and discusses some of the early findings of the Norfolk Island Carbon and Health Evaluation study designed to assess the impact of personal carbon trading on obesity and GHG emissions. Early results suggest that health and environmental scientists should be working more closely to develop cross-disciplinary initiatives and messages around health and environmental issues.